2021
DOI: 10.3390/genes12010066
|View full text |Cite
|
Sign up to set email alerts
|

The LDLR, APOB, and PCSK9 Variants of Index Patients with Familial Hypercholesterolemia in Russia

Abstract: Familial hypercholesterolemia (FH) is a common autosomal codominant disorder, characterized by elevated low-density lipoprotein cholesterol levels causing premature atherosclerotic cardiovascular disease. About 2900 variants of LDLR, APOB, and PCSK9 genes potentially associated with FH have been described earlier. Nevertheless, the genetics of FH in a Russian population is poorly understood. The aim of this study is to present data on the spectrum of LDLR, APOB, and PCSK9 gene variants in a cohort of 595 index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
0
18
0
5
Order By: Relevance
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this whole-exome study demonstrated the overrepresentation of several disease-causing variants for Mendelian disorders, such as phenylketonuria (PAH, rs5030858), Wilson's disease (ATP7B, rs76151636), factor VII deficiency (F7, rs36209567), and the kyphoscoliosis type of Ehlers-Danlos syndrome (FKBP14, rs542489955). For the Russian population, however, pathogenic variant frequencies were reported mostly for relatively small cohorts including patients and their families and targeted at specific genes and disorders, for example, familial hypercholesterolemia (Meshkov et al, 2021;Miroshnikova et al, 2021); cystic fibrosis, phenylketonuria, alpha-1 antitrypsin deficiency, and sensorineural hearing loss (Kiseleva et al, 2020;Petrova et al, 2020); cardiomyopathy (Marakhonov et al, 2019;Zaklyazminskaya et al, 2019;Kulikova et al, 2021;Shestak et al, 2021); and breast and ovarian cancer (Brovkina et al, 2018;Solodskikh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetic research on familial hypercholesterolemia in Russia has been conducted for more than 30 years in different regions of the country [29]. It is worth mentioning some variants of the LDLR gene that not only occur in most regions of Russia but are also the most common variants of this gene: rs121908038 and rs761954844 [28][29][30][31][32]57]. Additionally, these variants have been found in populations of Northern and Central Europe (rs121908038) and in populations of Central and Eastern Europe, Southeast Asia, and North America (rs761954844) [40].…”
Section: Discussionmentioning
confidence: 99%
“…The small sample sizes do not allow us to assess clinicalcourse features of the disease that are associated with various pathogenic variants in lipid metabolism genes and to evaluate the spectrum of pathogenic variants in lipid metabolism genes in the population of Russia. Targeted sequencing can be useful not only for rapid and cost-effective diagnosis of familial hypercholesterolemia, but also for investigation of rare variants of lipid metabolism genes and their influence on the patients' phenotype [30,57,58]. This method may help to combine the efforts of physicians and investigators from different regions for the research on familial hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Разработка полигенных шкал риска развития ХНИЗ (атеросклероза, АГ, СД, ожирения, остеопороза и др.) [21][22][23].…”
Section: распространенность семейной гиперхолестеринемииunclassified